Fine-structure Transitions of Ne+, Ar+, Ne2+, and Ar2+ Induced by Collisions with Atomic Hydrogen - Pei-Gen Yan; James F. Babb (The Astrophysical Journal, 2024)
We calculate cross sections for fine-structure transitions of Ne ^+ , Ar ^+ , Ne ^2+ , and Ar ^2+ in collisions with atomic hydrogen by using quantum-mechanical methods. Relaxation rate coefficients are calculated for temperatures up to 10,000 K. The temperature-dependent critical densities for the relaxation of Ne ^+ , Ar ^+ , Ne ^2+ , and Ar ^2+ in collisions with H have been determined and compared to the critical densities for collisions with electrons. The present calculations will be useful for studies utilizing the infrared lines [Ne ii ] 12.8, [Ne iii ] 15.6, [Ne iii ] 36.0, [Ar ii ] 6.99, [Ar iii ] 8.99, and [Ar iii ] 21.8 μ m as diagnostics of, for example, planetary nebulae and star formation.